PENGARUH PEMBINAAN, PELATIHAN DAN PENGEMBANGAN, PEMBERDAYAAN DAN PARTISIPASI TERHADAP KINERJA KARYAWAN (Studi Pada PT. Njonja Meneer Semarang) - Levy Kambey, Fendy; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2013)
Njonja Meneer company pointed out that the organization is already doingapplication coaching, training and development, empowerment and participation in theorganizational practices. But in applying coaching and empowerment of the variable isstill not carried out optimally. This is apparent from the results of the interviews alsoshowed that employees in the performance of Njonja Meneer company is still low. Thepurpose of this study was to analyze the influence of coaching, training and development,empowerment and participation on employee performance in PT. Njonja Meneer.The sample used in the study were sixty people. Data analysis method used ismultiple linear regression analysis using IBM SPSS 21. Sampling in this study based onterms the respondents established earlier that all employees and managers of high levelfrom all fields who have worked at least six months and have experienced the process oftraining development, and has been involved (participating) in decision making in NjonjaMeneer company.The results show that the coaching, training and development, empowerment andparticipation affect the performance of employees above fifty percent. From the results ofthe regression analysis training and development have the greatest influence on employeeperformance. That means training and development at Njonja Meneer company alreadydone well and have the most impact on employee performance than coaching,empowerment, and participation. While the smallest variable that affects employeeperformance is empowerment and coaching.